145 Helmet smart at head start: using an interactive and asynchronous helmet safety education initiative to promote behaviour change among head start children. (19th September 2017) - Wendt, Wendi-Jo; Alpert, Aviva; Folsom, Bethany N; Mott, Elizabeth; Hashikawa, Andrew
Abstract : Purpose: The 'Helmet Smart at Head Start (HS)' program was developed to promote helmet use among preschool children and to train caregivers about helmet safety and proper helmet fit. Methods: We developed a 3 min audiovisual podcast on helmet safety and proper fit. Events were held at two local HS centres in collaboration with Safe Kids. Each child received an adjustable helmet while caregivers watched the podcast and completed pre- and post- surveys assessing helmet-related attitudes and practices. A sample of caregivers were surveyed again 3 months after the event. Descriptive statistics were used for analysis. Results: In March 2016, over 200 children participated in the program. 50 caregivers viewed the podcast and completed the surveys. Pre-intervention, caregivers reported that their child did not always wear a helmet when using a bicycle (55%), tricycle (71%), or scooter (70%). Over 57% acknowledged their child did not own a helmet. After viewing the podcast, caregiver's comfort level in fitting a helmet increased from 78% to 94%. In an end-of-school-year, 3 month-post-event survey of caregivers (n=40) there was a reported continued increase in the percentage of children who always wore a helmet when riding a bicycle (45% to 86%), tricycle (29% to 61%), and scooter (30% to 81%). Conclusion: At an educational helmet safety event held in collaboration with community partners, injury prevention information was shared asynchronously and rapidly using on-demand videos. Providing children access to helmets appears to be a critical component in the promotion of helmet use in resource-poor settings. Significance: Community initiatives at HS centres with interactive, hand-on demonstrations and on-demand audiovisual materials can effectively disseminate injury prevention information that may lead to sustained home behaviour changes.